Pendidikan Karakter Dalam Pengentasan Aksi Bullying di SMA Negeri 9 Gowa - Nurdiana Sudirman; Sam’un Mukraimin; Maemunah Maemunah (LPPM Politeknik Pratama, 2023)
This research is a type of qualitative literature review research. The data used in this research is secondary data. Secondary data sources in question are in the form of books and primary or original scientific reports contained in online news articles or journals as relevant literature studies to study related to the phenomenon of bullying in schools to be analyzed. In order to investigate and understand an event or problem that has taken place in the midst of bullying at SMA 9 GOWA by collecting various kinds of information which is then processed to obtain a solution so that the cases that are revealed can be resolved. The researcher went out into the field to observe regarding the concept of opinion, rules, research on the experience of the situation from informants consisting of 2 people who were students of SMA Negeri 9 Gowa according to the criteria based on the data obtained. Furthermore, sociological data analysis was carried out and descriptions were developed on the basis of